1999
DOI: 10.1016/s0928-8244(98)00133-3
|View full text |Cite
|
Sign up to set email alerts
|

Aspergillus fumigatus catalases: cloning of an Aspergillus nidulans catalase B homologue and evidence for at least three catalases

Abstract: The presence of catalases in the water soluble fractions of three Aspergillus fumigatus strains was investigated using non-denaturing and denaturing polyacrylamide gel electrophoresis and Western analysis. Using non-denaturing polyacrylamide gel electrophoresis and staining for catalase activity, three separate catalases were identified. An A. fumigatus catalase gene (catB) was cloned from genomic DNA using the Aspergillus niger catR gene as a probe. Polyclonal antibodies were raised to a glutathione S-transfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…Prussian‐Blue‐stained PAGE gels revealed catalase bands at 160 kDa and 80 kDa in non‐denatured and denatured recombinant Bgh CATB samples, respectively. These correspond to the 160‐kDa band detected in recombinant Bgh protein and to the native Bgh 80‐kDa band with an anti‐CATB polyclonal antibody from A. fumigatus (Takasuka et al ., 1999) by Western analysis. Subsequent immunolocalization studies revealed that when the host is present most of the fungal CATB is secreted from the germ tube tips and leaches down on to the host.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Prussian‐Blue‐stained PAGE gels revealed catalase bands at 160 kDa and 80 kDa in non‐denatured and denatured recombinant Bgh CATB samples, respectively. These correspond to the 160‐kDa band detected in recombinant Bgh protein and to the native Bgh 80‐kDa band with an anti‐CATB polyclonal antibody from A. fumigatus (Takasuka et al ., 1999) by Western analysis. Subsequent immunolocalization studies revealed that when the host is present most of the fungal CATB is secreted from the germ tube tips and leaches down on to the host.…”
Section: Discussionmentioning
confidence: 82%
“…4Bc,d) and host replica surface (no living host present) (Fig. 4Be,f) at 20 hpi, exploiting the A. fumigatus polyclonal antibody anti‐CATB (Takasuka et al ., 1999). On epidermal strips, immunofluorescence was seen around the germ tube tips, more noticeably around the AGT tip (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, Aspergillus species have the ability to produce high levels of catalase and hyperoxide dismutase (Takasuka et al, 1999). This phenomenon has already been observed in AMB-resistant C. albicans strains that overproduce catalase and superoxide dismutase and were less sensitive to oxidative agents than AMB-sensitive C. albicans (Warnock et al, 1999;Moore et al, 2000a,b).…”
Section: Mechanisms Of Amb Resistancementioning
confidence: 77%
“…animals than to catalases from eubacteria and plants. In contrast, CatA and CatB, along with other enzymes up to now found only in filamentous fungi and eubacteria, form the largesubunit catalase family (5,8,13,15,23,24,27,37,48). In fact, endosymbiosis and horizontal gene transfer mechanisms have been invoked to explain the grouping of these fungal and bacterial catalases (24).…”
Section: Discussionmentioning
confidence: 99%